Ultra-high strength self-compacting sea sand mortar and preparation method thereof
By using specific combined materials and processes in self-compression mortar, ultra-high strength self-compression sea sand mortar with a flow degree of more than 300mm and a compressive strength of more than 120MPa was prepared, which solved the problem of difficult balance of fluidity and strength in the prior art. Good construction performance and volume stability are achieved, and the lack of river sand has been alleviated.
Patent Information
- Application Number
- CN202310351220.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-29
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2043-03-29
AI Technical Summary
The existing self-finished mortar is difficult to balance in terms of fluidity and strength, resulting in poor construction performance, low strength after condensation and hardening, and serious volume deformation, which makes it impossible to effectively repair the defects of ultra-high-strength concrete.
Using a combination of silicate cement, sulfoaluminate cement, fly ash, silica fume, gypsum, white stone powder, basalt fiber, redispersible latex powder, water reducer, defoaming agent and water retention agent, through specific The ratio and stirring process prepare ultra-high strength self-finished sea sand mortar to ensure that the flow degree is greater than 300mm and the compressive strength is greater than 120MPa.
It achieves a balance of flow and strength, has good permeability and fluidity, no vibration, no cracks, few pores, good volume stability, is suitable for defect repair of ultra-high-strength concrete, alleviating the lack of river sand , reducing transportation costs.
Smart Images

Figure CN116283192B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of self-compacting mortar, and in particular to an ultra-high strength self-compacting sea sand mortar and a preparation method thereof. Background Art
[0002] With the development of high-performance concrete, self-compacting concrete has attracted widespread attention for its excellent working performance, mechanical properties and durability. Self-compacting mortar is a special self-compacting concrete, and also a kind of high-strength grouting material. It is mainly used for reinforcement and repair of concrete structures, foundation reinforcement, prestressed duct grouting, etc. With the development of modernization of construction engineering, ultra-high performance concrete is gradually used. For some quality defects of ultra-high strength concrete that occur during the construction process, corresponding ultra-high strength mortar should be used to deal with the defects, but there is currently no mature ultra-high strength mortar for defect repair.
[0003] At present, domestic high-strength grouting materials are generally configured with special binders and high-strength aggregates. However, special binders are greatly restricted in engineering applications due to their limited production, short shelf life and high price. Ordinary silicate cement grouting materials are now mostly used, but there are problems such as poor construction performance, low strength after coagulation and hardening, and serious volume deformation. The product quality is difficult to guarantee, and there is a significant gap with the expected construction effect, which can easily cause the failure of ultra-high concrete quality defect repair or failure after long-term action. It is difficult for ultra-high strength self-compacting mortar to meet high requirements in fluidity and strength at the same time. If a higher fluidity is required, strength must be sacrificed. When the mortar strength is high, the fluidity is poor. Therefore, it is of great engineering practical significance to study mortar with self-compacting properties and ultra-high strength as a grouting material. Summary of the invention
[0004] In view of the above problems, the present application is proposed to provide an ultra-high strength self-compacting sea sand mortar that overcomes the above problems or at least partially solves the above problems, comprising:
[0005] A super-high strength self-compacting sea sand mortar comprises the following components, calculated by weight: 300-400 parts of silicate cement, 80-150 parts of sulphoaluminate cement, 50-100 parts of fly ash, 30-50 parts of silica fume, 10-30 parts of gypsum, 30-50 parts of white stone powder, 2-10 parts of basalt fiber, 600-700 parts of sea sand, 8-15 parts of redispersible latex powder, 5-10 parts of water reducer, 1-2 parts of defoamer, 1-3 parts of water retaining agent and 220-280 parts of water.
[0006] Preferably, the average particle size of the redispersible latex powder is 80 μm, and the viscosity of a 50% aqueous solution is not less than 10.
[0007] Preferably, the SiO in the silica ash 2The content is ≥96%, and the 28d activity index is 113%.
[0008] Preferably, the fly ash is primary ash, the residue on a 45 μm square sieve is 10%, and the 28-day activity is 122%.
[0009] Preferably, the basalt fiber is chopped basalt fiber with a fiber length of 10 to 20 mm and a density of 2.5 g / cm 3 .
[0010] Preferably, the sea sand is fine sand with a fineness modulus of 1.5-2.5 and a particle size not greater than 5 mm.
[0011] Preferably, the water reducer is a polycarboxylic acid high-efficiency water reducer with a solid content of 38% and a water reduction rate of 30%.
[0012] Preferably, the defoaming agent is a polyether-modified polysiloxane defoaming agent.
[0013] Preferably, the water retaining agent is hydroxypropyl methylcellulose.
[0014] The present application also provides a method for preparing ultra-high strength self-compacting sea sand mortar, comprising the steps of:
[0015] Mixing the water reducing agent, the defoaming agent, the water retaining agent and the water in a first specified ratio to obtain an admixture aqueous solution;
[0016] The silicate cement, the sulphoaluminate cement, the fly ash, the silica fume, the gypsum, the white stone powder, the redispersible latex powder and the basalt fiber are mixed and stirred for 3 minutes according to the second specified ratio, and half of the admixture aqueous solution is added and mixed and stirred slowly for 3 minutes, and finally the remaining half of the admixture aqueous solution is added and stirred quickly for 6 minutes to obtain sea sand mortar;
[0017] The sea sand mortar is poured into a mold for forming, and a film is covered on the surface of the test mold after forming. The mold is demoulded after 24 hours, and cured under standard conditions to a specified age.
[0018] This application has the following advantages:
[0019] In the embodiments of the present application, relative to the problem of the unbalanced fluidity and strength of the self-compacting mortar in the prior art, the present application provides a solution for balancing the fluidity and strength of the self-compacting mortar, specifically: calculated by mass, including the following components: 300-400 parts of silicate cement, 80-150 parts of sulphoaluminate cement, 50-100 parts of fly ash, 30-50 parts of silica fume, 10-30 parts of gypsum, 30-50 parts of white stone powder, 2-10 parts of basalt fiber, 600-700 parts of sea sand, 8-15 parts of redispersible latex powder, 5-10 parts of water reducer, 1-2 parts of defoamer, 1-3 parts of water retainer and 220-280 parts of water. Through the above technical solution, the present invention has the following beneficial effects:
[0020] 1. It can simultaneously meet the characteristics of high fluidity and ultra-high strength, with a fluidity greater than 300mm and a compressive strength greater than 120MPa. It has good impermeability and fluidity, no need for vibration, no cracks, few and small pores, self-compacting ability, and good volume stability. It can be used to repair defects in ultra-high-strength concrete, filling the technical gap of ultra-high-strength self-compacting mortar;
[0021] 2. The raw materials are easy to obtain, and there is no need to use high-strength aggregates. By adding admixtures and admixtures, combined with the mix ratio design, a mortar with self-compacting properties, micro-expansion properties and ultra-high strength is prepared. The preparation process is simple and easy to construct on site;
[0022] 3. Replacing or partially replacing river sand with sea sand can alleviate the shortage of river sand, use local materials and save transportation costs. The price of untreated sea sand is only 1 / 3 to 1 / 4 of that of river sand, thus realizing high-value utilization of sea sand resources. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the technical solution of the present application, the following is a brief introduction to the drawings required for use in the description of the present application. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.
[0024] Figure 1 This is a step flow chart of a method for preparing ultra-high strength self-compacting sea sand mortar provided in one embodiment of the present application. DETAILED DESCRIPTION
[0025] In order to make the objects, features and advantages of the present application more obvious and understandable, the present application is further described in detail below in conjunction with the accompanying drawings and specific implementation methods. Obviously, the described embodiments are part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present application.
[0026] An ultra-high strength self-compacting sea sand mortar provided in an embodiment of the present application includes the following components, calculated by weight: 300-400 parts of silicate cement, 80-150 parts of sulphoaluminate cement, 50-100 parts of fly ash, 30-50 parts of silica fume, 10-30 parts of gypsum, 30-50 parts of white stone powder, 2-10 parts of basalt fiber, 600-700 parts of sea sand, 8-15 parts of redispersible latex powder, 5-10 parts of water reducer, 1-2 parts of defoamer, 1-3 parts of water retaining agent and 220-280 parts of water.
[0027] In the embodiments of the present application, relative to the problem of unbalanced fluidity and strength of self-compacting mortar in the prior art, the present application provides a solution for balancing the fluidity and strength of self-compacting mortar, specifically: calculated by mass, including the following components: 300-400 parts of silicate cement, 80-150 parts of sulphoaluminate cement, 50-100 parts of fly ash, 30-50 parts of silica fume, 10-30 parts of gypsum, 30-50 parts of white stone powder, 2-10 parts of basalt fiber, 600-700 parts of sea sand, 8-15 parts of redispersible latex powder, 5-10 parts of water reducer, 1-2 parts of defoamer, 1-3 parts of water retaining agent and 220-280 parts of water. The self-compacting mortar of the present invention has a fluidity greater than 300 mm and a compressive strength greater than 120 MPa, has good impermeability and fluidity, and uses simple and easily available raw materials, does not require the use of high-strength aggregates, has a simple preparation process and is easy to construct on site, and uses sea sand to replace or partially replace river sand, which can alleviate the shortage of river sand, obtain materials locally, and save transportation costs.
[0028] Next, an ultra-high strength self-compacting sea sand mortar in this exemplary embodiment will be further described.
[0029] In one embodiment of the present application, the average particle size of the redispersible latex powder is 80 μm, and the viscosity of a 50% aqueous solution is not less than 10.
[0030] Specifically, the present invention uses gypsum as the main base material, PⅡ42.5 silicate cement and sulphoaluminate cement as the main setting materials, and then combines with redispersible latex powder and mineral admixtures (fly ash, silica fume and white stone powder) as a setting system, the components complement each other and have a good bonding effect. As a rheology modifier, the redispersible latex powder has strong adhesion, which can not only improve the cohesion of gypsum-based materials, improve fluidity, prevent water seepage and segregation, but also give the gypsum-based self-leveling material good deformability, which helps to improve the adhesion between the repair mortar and the interface, and the mortar solidification and polymer film formation are carried out simultaneously, which significantly improves the compactness of the repair mortar, thereby improving the mortar's impermeability and antifreeze properties.
[0031] The fluidity of the mortar increases first and then decreases with the increase of the amount of redispersible latex powder. This is because when the amount is small, the active substances on the surface of the redispersible latex powder will introduce tiny bubbles, improve the slurry's ability to suspend components, play a lubricating role, and increase the cohesion of the mortar, thereby increasing the fluidity. However, excessive redispersible latex powder will consume a large amount of free water in the slurry, increase the viscosity of the slurry, and reduce the fluidity.
[0032] The strength of the mortar decreases and then increases with the increase of the amount of redispersible latex powder. This is because the surfactant of the redispersible latex powder introduces a large number of tiny bubbles, and the air entraining effect plays a dominant role at this time. This improves the workability of the self-compacting mortar to a certain extent, but it will cause a large number of pores to exist inside the slurry in the early stage of hardening, which will lead to a decrease in early strength.
[0033] Therefore, it is difficult to balance the strength and fluidity of the mortar. However, the present invention uses a redispersible latex powder with an average particle size of 80 μm and a dosage of 0.6%-0.8%, and adds raw materials such as admixtures and mineral admixtures in a specified ratio, so that the mortar prepared by the present invention meets the characteristics of high fluidity and ultra-high strength, with a fluidity greater than 300 mm and a compressive strength greater than 120 MPa.
[0034] In one embodiment of the present application, the SiO 2 The content is ≥96%, and the 28d activity index is 113%; in one embodiment of the present application, the fly ash is primary ash, the 45μm square hole sieve residue is 10%, and the 28-day activity is 122%.
[0035] Specifically, the silica fume may be any one or more silica fume that meets the requirements of GB / T27690 "Silica fume for mortar and concrete", including ordinary silica fume and / or modified silica fume. Fly ash particles have a porous honeycomb structure, a large specific surface area, high adsorption activity, and strong water absorption, which improves the workability of the mortar. Under the synergistic effect of mineral admixtures, basalt fibers and the redispersible latex powder, the volume stability and crack resistance of the mortar can be improved.
[0036] In one embodiment of the present application, the basalt fiber is a short chopped basalt fiber with a fiber length of 10 to 20 mm and a density of 2.5 g / cm 3 Specifically, the basalt fiber as a raw material can prevent the mortar from forming cracks and reduce the porosity of the mortar.
[0037] In one embodiment of the present application, the sea sand is fine sand with a fineness modulus of 1.5-2.5 and a particle size of no more than 5 mm. Specifically, aggregate is a granular loose material that plays a skeleton or filling role in concrete, and plays a skeleton and supporting role in buildings. Using sea sand as aggregate can not only greatly improve the wear resistance of the hardened gypsum body, reduce deformation, and reduce the generation of cracks to a certain extent, but also reduce the overall cost of the material, without the need for grading, the preparation process is simple and easy to construct on site. And because river sand resources are in short supply, and sea sand is widely distributed, rich in resources, and convenient for sea transportation, the proportion of sea sand in the utilization of building sand and gravel resources is increasing. The Cl present in sea sand - It will accelerate the hardening of mortar, improve the early strength of mortar, and improve construction efficiency. Replacing or partially replacing river sand with sea sand can alleviate the shortage of river sand. The price of untreated sea sand is only 1 / 3 to 1 / 4 of that of river sand, which saves costs.
[0038] In one embodiment of the present application, the water reducer is a polycarboxylic acid high-efficiency water reducer with a solid content of 38% and a water reduction rate of 30%. Specifically, a water reducer is a concrete admixture that can reduce the amount of mixing water while maintaining the slump of concrete substantially unchanged. Self-leveling mortar should have excellent flow properties. Without increasing the amount of mixing water, the addition of a water reducer can greatly improve the fluidity and hardening strength of the mortar slurry, and at the same time improve the mortar slurry's resistance to water seepage and segregation and sedimentation, while also reducing the unit cement dosage and saving cement.
[0039] In one embodiment of the present application, the defoamer is a polyether-modified polysiloxane defoamer; specifically, the self-leveling mortar formula contains organic polymer admixtures such as water reducer, rubber powder and water retaining agent. When stirred at high speed, the slurry is very likely to generate a large number of bubbles and is not easy to break. Adding a trace amount of defoamer can inhibit the formation of bubbles during stirring, improve the basic properties of the mortar, and compensate for the reduction in mortar strength. The present invention uses a polyether-modified polysiloxane defoamer, which can effectively prevent or destroy the generation of bubbles in the aqueous system.
[0040] In one embodiment of the present application, the water retaining agent is hydroxypropyl methylcellulose; specifically, adding a water retaining agent to the self-leveling material can effectively control the self-leveling material from losing water too quickly, which may cause insufficient material hydration, reduced strength, surface powdering, cracking, and the like.
[0041] Reference Figure 1 , showing a method for preparing an ultra-high strength self-compacting sea sand mortar provided in one embodiment of the present application;
[0042] The method comprises:
[0043] S110, mixing the water reducing agent, the defoaming agent, the water retaining agent and the water according to a first specified ratio to obtain an admixture aqueous solution;
[0044] As an example, 5-10 parts of water reducing agent, 1-2 parts of defoaming agent, 1-3 parts of water retaining agent and 220-280 parts of water are weighed, stirred evenly in a container for later use, to obtain the admixture aqueous solution.
[0045] S120, mixing the silicate cement, the sulphoaluminate cement, the fly ash, the silica fume, the gypsum, the white stone powder, the redispersible latex powder and the basalt fiber according to the second specified ratio for 3 minutes, adding half of the admixture aqueous solution and mixing slowly for 3 minutes, and finally adding the remaining half of the admixture aqueous solution and mixing rapidly for 6 minutes to obtain sea sand mortar;
[0046] As an example, weigh 300-400 parts of PⅡ42.5 silicate cement, 80-150 parts of sulphoaluminate cement, 50-100 parts of fly ash, 30-50 parts of silica fume, 10-30 parts of gypsum, 30-50 parts of white stone powder, 8-15 parts of redispersible latex powder, and 2-10 parts of basalt fiber, pour them into a stirring pot and mix and stir for 3 minutes. After stirring evenly, add half of the aqueous solution of the additive obtained in step S110, stir slowly for 3 minutes, and finally add the remaining half of the aqueous solution of the additive obtained in step S110, stir quickly for 6 minutes to obtain a slurry.
[0047] S130, pouring the sea sand mortar into a mold to form it, covering the surface of the test mold with a film after forming, demoulding after 24 hours, and curing it under standard conditions to a specified age;
[0048] Specifically, the stirred slurry is poured into a mold for forming, a film is covered on the surface of the test mold after forming, and the mold is demolded after 24 hours. After demolding, the test piece is cured under standard conditions to a specified age.
[0049] Example 1
[0050] Weigh each component according to the mix ratio in Table 1, wherein the fly ash is first-grade ash, the 45μm square hole sieve residue is 10%, the 28-day activity is 122%, and the silica ash SiO 2 The content is ≥96%, the 28d activity index is 113%, the basalt fiber is short-cut basalt fiber, the fiber length is 10-20mm, and the density is 2.5g / cm 3 ;
[0051] The sea sand is fine sand with a fineness modulus of 1.5-2.5 and a particle size not greater than 5mm. The average particle size of the redispersible latex powder is 80μm, and the annual concentration of 50% aqueous solution is not less than 10. The water reducer is a polycarboxylic acid high-efficiency water reducer with a solid content of 38% and a water reduction rate of 30%. The defoamer is a polyether modified polysiloxane defoamer; and the water retaining agent is hydroxypropyl methylcellulose.
[0052]
[0053]
[0054] Table 1
[0055] Performance test results: fluidity is 323mm and 28-day compressive strength is 128MPa.
[0056] Example 2
[0057] Weigh each component according to the mix ratio in Table 2, wherein the fly ash is first-grade ash, the 45μm square hole sieve residue is 10%, the 28-day activity is 122%, and the silica ash SiO 2 The content is ≥96%, the 28d activity index is 113%, the basalt fiber is short-cut basalt fiber, the fiber length is 10-20mm, and the density is 2.5g / cm 3 ;
[0058] The sea sand is fine sand with a fineness modulus of 1.5-2.5 and a particle size not greater than 5mm. The average particle size of the redispersible latex powder is 80μm, and the annual concentration of 50% aqueous solution is not less than 10. The water reducer is a polycarboxylic acid high-efficiency water reducer with a solid content of 38% and a water reduction rate of 30%. The defoamer is a polyether modified polysiloxane defoamer; and the water retaining agent is hydroxypropyl methylcellulose.
[0059]
[0060] Table 2
[0061] Performance test results: The measured fluidity is 311mm and the 28-day compressive strength is 134MPa.
[0062] Example 3
[0063] Weigh each component according to the mix ratio in Table 3, wherein the fly ash is first-grade ash, the 45μm square hole sieve residue is 10%, the 28-day activity is 122%, and the silica ash SiO 2 The content is ≥96%, the 28d activity index is 113%, the basalt fiber is short-cut basalt fiber, the fiber length is 10-20mm, and the density is 2.5g / cm 3 ;
[0064] The sea sand is fine sand with a fineness modulus of 1.5-2.5 and a particle size not greater than 5mm. The average particle size of the redispersible latex powder is 80μm, and the annual concentration of 50% aqueous solution is not less than 10. The water reducer is a polycarboxylic acid high-efficiency water reducer with a solid content of 38% and a water reduction rate of 30%. The defoamer is a polyether modified polysiloxane defoamer; and the water retaining agent is hydroxypropyl methylcellulose.
[0065]
[0066] Table 3
[0067] Performance test results: The measured fluidity is 330mm and the 28-day compressive strength is 126MPa.
[0068] The performance tests of Examples 1-3 all referred to the provisions of JC / T 1023-2021 "Gypsum-based self-leveling mortar" to test fluidity and compressive strength. The properties of the measured ultra-high strength self-compacting sea sand mortar all meet the relevant properties specified in the standard JC / T 2381-2016 "Repair Mortar". The prepared ultra-high strength self-compacting sea sand mortar has a fluidity greater than 300 mm and a compressive strength greater than 120 MPa, and has good impermeability and fluidity.
[0069] Although the preferred embodiments of the present application have been described, those skilled in the art may make additional changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the embodiments of the present application.
[0070] Finally, it should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or terminal device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or terminal device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or terminal device including the elements.
[0071] The above is a detailed introduction to an ultra-high strength self-compacting sea sand mortar and a preparation method thereof provided by the present application. Specific examples are used herein to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the method of the present application and its core idea; at the same time, for general technical personnel in this field, according to the idea of the present application, there will be changes in the specific implementation method and application scope. In summary, the content of this specification should not be understood as a limitation on the present application.
Claims
1. An ultra-high strength self-compacting sea sand mortar, characterized in that: Calculated by weight, it includes the following components: 300-400 parts of silicate cement, 80-150 parts of sulphoaluminate cement, 50-100 parts of fly ash, 30-50 parts of silica fume, 10-30 parts of gypsum, 30-50 parts of white stone powder, 2-10 parts of basalt fiber, 600-700 parts of sea sand, 8-15 parts of redispersible latex powder, 5-10 parts of water reducing agent, 1-2 parts of defoaming agent, 1-3 parts of water retaining agent and 220-280 parts of water; The average particle size of the redispersible latex powder is 80 μm, and the viscosity of a 50% aqueous solution is not less than 10.
2. The ultra-high strength self-compacting sea sand mortar according to claim 1, characterized in that: The content of SiO2 in the silica ash is ≥96%, and the 28d activity index is 113%.
3. The ultra-high strength self-compacting sea sand mortar according to claim 1, characterized in that: The fly ash is first-grade ash, the residue on a 45 μm square sieve is 10%, and the activity after 28 days is 122%.
4. The ultra-high strength self-compacting sea sand mortar according to claim 1, characterized in that: The basalt fiber is short-cut basalt fiber with a fiber length of 10 to 20 mm and a density of 2.5 g / cm 3 .
5. The ultra-high strength self-compacting sea sand mortar according to claim 1, characterized in that: The sea sand is fine sand with a fineness modulus of 1.5-2.5 and a particle size not greater than 5 mm.
6. The ultra-high strength self-compacting sea sand mortar according to claim 1, characterized in that: The water reducing agent is a polycarboxylic acid high-efficiency water reducing agent with a solid content of 38% and a water reducing rate of 30%.
7. The ultra-high strength self-compacting sea sand mortar according to claim 1, characterized in that: The defoamer is a polyether-modified polysiloxane defoamer.
8. The ultra-high strength self-compacting sea sand mortar according to claim 1, characterized in that: The water retaining agent is hydroxypropyl methylcellulose.
9. A method for preparing the ultra-high strength self-compacting sea sand mortar according to any one of claims 1 to 8, characterized in that: Includes steps: Mixing the water reducing agent, the defoaming agent, the water retaining agent and the water in a first specified ratio to obtain an admixture aqueous solution; The silicate cement, the sulphoaluminate cement, the fly ash, the silica fume, the gypsum, the white stone powder, the redispersible latex powder and the basalt fiber are mixed and stirred for 3 minutes according to the second specified ratio, and half of the admixture aqueous solution is added and mixed and stirred slowly for 3 minutes, and finally the remaining half of the admixture aqueous solution is added and stirred quickly for 6 minutes to obtain sea sand mortar; The sea sand mortar is poured into a mold for forming, and a film is covered on the surface of the test mold after forming. The mold is demoulded after 24 hours, and cured under standard conditions to a specified age.
Citation Information
Patent Citations
Self-leveling mortar mixed with desalted sea sand
CN106587873A
High-fluidity ultrahigh-strength cement-based grouting material and preparation method thereof
CN113292300A